Biodiversity conservation in traditional farming landscapes - Dorresteijn, Ine (2015)
Traditional farming landscapes typically support exceptional biodiversity. They evolved as tightly coupled social-ecological systems, in which traditional human land-use shaped highly heterogeneous landscapes. However, these landscapes are under severe threats of land-use change which potentially pose direct threats to biodiversity, in particular through land-use intensification and land abandonment. Navigating biodiversity conservation in such changing landscapes requires a thorough understanding of the drivers that maintain the social-ecological system. This dissertation aimed to identify system properties that facilitate biodiversity conservation in traditional farming landscape, focusing specifically on birds and large carnivores in the rapidly changing traditional farmland region of Southern Transylvania, Romania. In order to identify these properties, I first examined the effects of local and landscape scale land-use patterns on birds and large carnivores and how they may be affected by future land-use change (Chapters II-V). Second, to gauge the role of particular traditional land-use elements for biodiversity I focused on the conservation value of traditional wood pastures (Chapters VI-VIII). Third, I took a social-ecological systems approach to understand how links between the social and ecological parts of the system affect human-bear coexistence (Chapters IV and IX). Bird diversity was supported by the broad gradients of woody vegetation cover and compositional heterogeneity. Land-use intensification, and hence the loss of woody vegetation cover and homogenization of land covers, would thus negatively affect biodiversity. This was especially evident from predictions on the distribution of the corncrake (Crex crex) in response to potential future land cover homogenization. Here, a moderate reduction of land cover diversity could drastically reduce the extent of corncrake habitat. Further results showed that the brown bear (Ursus arctos) would mainly be affected by land-use change through the ...